2014
DOI: 10.3390/md12084539
|View full text |Cite
|
Sign up to set email alerts
|

Marine Sponge Derived Natural Products between 2001 and 2010: Trends and Opportunities for Discovery of Bioactives

Abstract: Marine sponges belonging to the phylum Porifera (Metazoa), evolutionarily the oldest animals are the single best source of marine natural products. The present review presents a comprehensive overview of the source, taxonomy, country of origin or geographical position, chemical class, and biological activity of sponge-derived new natural products discovered between 2001 and 2010. The data has been analyzed with a view to gaining an outlook on the future trends and opportunities in the search for new compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
300
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(308 citation statements)
references
References 178 publications
(229 reference statements)
3
300
0
5
Order By: Relevance
“…Recent studies have reported the isolation of novel anticancer, antiviral, antibacterial, antifungal, antiprotozoal, anthelmintic, anti-inflammatory, immunosuppressive, antifouling and a range of other bioactive compounds from marine species (Majali et al, 2015;El Amraoui et al, 2014;Mehbub et al, 2014). In the present study, the antimicrobial and anti-oxidant properties of seven marine sponges are described.…”
Section: Antimicrobial and Anti-oxidant Potentials Of Marine Sponges mentioning
confidence: 93%
“…Recent studies have reported the isolation of novel anticancer, antiviral, antibacterial, antifungal, antiprotozoal, anthelmintic, anti-inflammatory, immunosuppressive, antifouling and a range of other bioactive compounds from marine species (Majali et al, 2015;El Amraoui et al, 2014;Mehbub et al, 2014). In the present study, the antimicrobial and anti-oxidant properties of seven marine sponges are described.…”
Section: Antimicrobial and Anti-oxidant Potentials Of Marine Sponges mentioning
confidence: 93%
“…and Ircinia sp. were found to be the most promising genera because of their capacity for producing new bioactive compounds [12]. Considering this, the primary objective of the study was to detect the pharmaceutical applications of the marine sponge Sigmadocia pumila (S. pumila).…”
Section: Introductionmentioning
confidence: 99%
“…Marine organisms are regarded as the largest unexplored source of bioactive compounds, and their biotechnological potential has resulted in extensive evaluation of their biological activities (Bhakuni and Rawat, 2006;Rocha et al, 2015;Suleria et al, 2015). However, the number of compounds isolated from marine organisms is heavily weighted in favor of lipid (or organic solvent)-soluble agents or compounds with medium polarity (Bhakuni and Rawat, 2006;Mehbub et al, 2014;Rocha et al, 2015). This might be due to the difficulties associated with the isolation and purification of water-soluble compounds.…”
Section: Introductionmentioning
confidence: 99%